International Monetary Fund Annual Report 1946. (Annual Report of the Executive Board; Annual Report of the Executive Board, 1946)
This paper reviews key findings of the IMF's Annual Report for the fiscal year ended September 1946. This report covers the operations and policies of the IMF in the period from May 6, 1946, when the Executive Directors held their first meeting in Washington, through early September 1946. Since it is intended that in future years the annual report of the Executive Directors will cover the operations of the IMF in the preceding fiscal year, such figures as are here presented deal mainly with the period ending June 30, 1946.